Artificial lipid membrane permeability method for predicting intestinal drug transport: Probing the determining step in the oral absorption of sulfadiazine; Influence of the formation of binary and ternary complexes with cyclodextrins - Delrivo, Alicia (2018)
We propose an in vitro permeability assay by using a modified lipid membrane to predict the in vivo intestinal passive permeability of drugs. Two conditions were tested, one with a gradient pH (pH 5.5-donor/pH 7.4-receptor) and the other with an iso-pH 7.4. The predictability of the method was established by correlating the obtained apparent intestinal permeability coefficients (Papp) and the oral dose fraction absorbed in humans (fa) of 16 drugs with different absorption properties. The Papp values correlated well with the absorption rates under the two conditions and the method showed high predictability and good reproducibility. On the other hand, with this method, we successfully predicted the transport characteristics of oral sulfadiazine (SDZ). Also, the tradeoff between the increase in the solubility of SDZ by its complex formation with cyclodextrins and/or aminoacids and its oral permeability was assessed. Results suggest that SDZ is transported through the gastrointestinal epithelium by passive diffusion in a pH-dependent manner. These results support the classification of SDZ as a high/low borderline permeability compound and are in agreement with the Biopharmaceutics Classification Systems (BCS). This conclusion is consistent with the in vivo pharmacokinetic properties of SDZ.